2020
DOI: 10.1080/09540105.2020.1742667
|View full text |Cite
|
Sign up to set email alerts
|

Green chicory leaf extract exerts anti-inflammatory effects through suppressing LPS-induced MAPK/NF-κB activation and hepatoprotective activity in vitro

Abstract: Green chicory (Cichorium intybus) leaf is consumed worldwide that has tremendous bio-functional activities. This study was designed to elucidate the bio-functional activities of the green chicory leaf extract (CLE). Trolox equivalent antioxidant activities were carried out against DPPH, ABTS radical scavenging and ferric reducing activities. CLE showed remarkable hepatoprotective activity against oxidative damages and reactive oxygen species reducing effect in RAW 264.7 and Hep G2 cells. The anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Lettuce and chicory plants that were more mechanically stimulated (Tables 1 and 2), i.e., exposed to MIS, also showed higher levels of polyphenolic compounds, especially total phenols and flavonoids. It should be emphasized that regardless of the mechanical treatment, i.e., MIS, the samples of lettuce and green chicory are rich in polyphenolic compounds and the results of total phenolics (TPC) are generally in agreement with other literature data, with the values of polyphenolic compounds obtained in this study for lettuce and green chicory not mechanically treated (control samples) similar or slightly lower than the data reported by other authors [36][37][38][39][40]. Based on the results obtained, it can be concluded that mechanical stimulation induces plant responses in direct response to stress exposure, as evidenced by the increased content of polyphenolic compounds in the lettuce and chicory samples in the MC treatments.…”
Section: Specialized Metabolites Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…Lettuce and chicory plants that were more mechanically stimulated (Tables 1 and 2), i.e., exposed to MIS, also showed higher levels of polyphenolic compounds, especially total phenols and flavonoids. It should be emphasized that regardless of the mechanical treatment, i.e., MIS, the samples of lettuce and green chicory are rich in polyphenolic compounds and the results of total phenolics (TPC) are generally in agreement with other literature data, with the values of polyphenolic compounds obtained in this study for lettuce and green chicory not mechanically treated (control samples) similar or slightly lower than the data reported by other authors [36][37][38][39][40]. Based on the results obtained, it can be concluded that mechanical stimulation induces plant responses in direct response to stress exposure, as evidenced by the increased content of polyphenolic compounds in the lettuce and chicory samples in the MC treatments.…”
Section: Specialized Metabolites Contentsupporting
confidence: 92%
“…Based on the above mentioned and obtained results, it can be concluded that that cultivated leafy vegetables abound antioxidants and thus present a high value nutritional raw material. According to other studies, the lettuce and green chicory species analyzed in this study, regardless of MIS, are vegetables that have significant antioxidant properties, i.e., high levels of antioxidant capacity [32,37,47].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…5). Blocking the phosphorylation of IκBα inhibits NF-κB nuclear translocation and represses the COX-2 [35,36]. In the present study, sandalwood oil could effectively inhibit COX-2 expression by effectively reducing the activation of the NF-κB signaling pathway in RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 50%
“…Ethanolic extract fraction Antioxidant activity [111] Tannins Anti-diabetic [40] Aqueous extracts Cardioprotective [112] Cichoric acid Anti-hepatitis B [113] Ethanol extract Anti-inflammatory [114] Aqueous extract Bone protection [115] Aqueous-alcoholic macerate Anti-proliferative [116] Hydroalcholic extract Hepatoprotective [117] Aqueous & ethanolic extract Anti-ulcer [94] Crude hydrophilic extracts Antioxidant [89]…”
Section: Leafmentioning
confidence: 99%